Socialization of TB Zero Program During The COVID-19 Pandemic for Residents of Islamic Center Residences in Kediri - Assolychatu Jaroh; Titien Siwi Hartayu (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
Tuberculosis (TB) problem is still a challenge for Indonesia today. The World Health Organization reports that Indonesia is the third country with the highest TB burden globally. All component of society must take a role in dealing with the global TB problem to achieve Zero TB in 2050. As the implementation, the Pesantren 2 Primary Health Care conducted socialization in the Wali Barokah Islamic Center, Kediri City. Socialization about knowledge to residents of Islamic Center, this study aims to determine the essential characteristics of Islamic Center residents against TB disease. Questionnaires related to knowledge were filled out before and after explanation using PowerPoint and leaflet media. By using purposive, sampling method obtained 100 respondents. The survey results showed a significant increase in the knowledge of Islamic Center residents about TB disease after socialization in terms of signs and symptoms of the disease (p 0.02), modes of transmission (p 0.02), and methods of prevention of transmission (p 0.01). Negative attitudes are still visible by stigmatizing TB sufferers from being ostracized (62.7%). The majority of subjects will go to health facilities (6.9%), but subjects still choose not to go for treatment (68%). The presentation of material about TB leads to reduce the burden of TB disease in TB endemic communities by modifying attitudes and behavior.